Adaptive thermal comfort in the two college campuses of Salesian College, Darjeeling – Effect of difference in altitude. (15th November 2016) - Thapa, Samar; Bansal, Ajay Kr.; Panda, Goutam Kr.
Abstract: Thermal comfort standards help building designers to provide good indoor climate as well as optimization of energy consumption in a building. Usually, Predicted Mean Vote (PMV) model which had its basis on the extensive climate chamber experiments is utilized to estimate the comfort condition for a building. However, the recent studies in the field of thermal comfort shows that the commonly used PMV model frequently underestimates and overestimates the thermal sensation in cooler and warmer condition in the real conditions leading to a more extreme set point temperature than required thus with higher energy consumption. This discrepancy in predicted and actual sensation was explained by the adaptive theory researches where the subjects have various adaptive opportunities to make themselves more comfortable than as predicted. However, the field survey based adaptive comfort standards depend upon several factors like the local climatic condition, ethnicity, etc. In this paper, we present the results of adaptive thermal comfort based field study conducted on two campuses of the same institution separated by altitude. A total of 1147 datasets were collected from 356 subjects with age group 18–29 years, most of whom were college students. We have discussed the variation of clothing insulation and thermal neutrality both with the altitude and with outdoor conditions. A wider range of indoor temperature for which the subjects voted neutral was seen especially on the lower side (12.5°–32.3 °C) in comparison to previous studies. Highlights: Conducted an ASHRAE class II Protocol based field study. 2 naturally ventilated college campus buildings. Buildings located at different altitude in Darjeeling. Differences in clothing insulation and thermal neutrality observed. Both with outdoor conditions and with altitude. Obtained steeper slope than de Dear and Brager adaptive equation. Suggested a higher adaptation of the subjects.